Program Management of Food Assistance for Single-Elderly Households in Bojongkoneng Village, Ngamprah District, West Bandung Regency - Hanifah, Hana Nida; Susilowati, Ellya; Rosilawati, Rosilawati; Pradytia, Wendy (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2025)
Single elderly individuals represent a vulnerable group facing physical, economic, and social limitations in meeting their basic needs, including access to nutritious food. The food assistance program organized by the Ministry of Social Affairs through a community-based approach serves as a strategic solution to enhance the welfare of the elderly. This study aims to analyze the management of the food assistance program for single elderly individuals in Bojongkoneng Village, Ngamprah Subdistrict, based on the four management functions by George R. Terry: planning, organizing, actuating, and controlling. The research employs a descriptive qualitative method with data collection techniques including in-depth interviews, observation, and document study involving eight key informants. The findings indicate that the program has been implemented systematically but remains suboptimal and lacks standardization across all managerial aspects. The main issues include the absence of individual assessments, unclear recruitment standards for community groups (Pokmas), lack of technical and occupational safety procedures (SOPs), and a weak monitoring and evaluation system. This study recommends the development of elderly needs assessments, formulation of SOPs, and strengthening of Pokmas institutional capacity and data-based supervision systems to improve the quality and sustainability of elderly food assistance programs.